Development of Pobara (Joyful Reading Tree) Media to Improve Letter Recognition Skills in Early Childhood: Integrating Islamic Pedagogical Values - Erika Melany; Rosa Imani Khan; Epritha Kurnia Wati (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Letter recognition constitutes one of the most fundamental pillars of early literacy development in early childhood, as it underlies phonological awareness and later reading competence. In practice, however, letter-learning activities in many early childhood classrooms are still delivered through conventional, text-based, and repetitive methods that fail to sustain children's engagement and motivation. Within Islamic educational thought, literacy acquisition is also inseparable from the theological command to read (iqra') articulated in the first revelation of the Qur'an, positioning the pursuit of knowledge as an act of worship rather than a merely secular skill. Motivated by these considerations, this study aimed to develop POBARA (Joyful Reading Tree), a three-dimensional instructional medium designed to improve letter recognition skills among young children through developmentally appropriate, play-based, and multisensory activities. The study employed a Research and Development (R&D) approach adapted from the Borg and Gall model, encompassing five stages: research and information gathering, planning, preliminary product development, expert validation, and product revision. The resulting prototype, a tree-shaped medium equipped with detachable illustrated alphabet cards, was validated by two instructional media experts and two early childhood education experts using structured questionnaires analyzed through Aiken's V formula. Results showed that all validation indicators exceeded the minimum acceptable coefficient of 0.75, confirming that POBARA is structurally durable and pedagogically appropriate for classroom use.